Neurometabolic and electrophysiological changes during cortical spreading depolarization: multimodal approach based on a lactate-glucose dual microbiosensor arrays - Cátia F. Lourenço (Nature Portfolio, 2017)
Abstract Spreading depolarization (SD) is a slow propagating wave of strong depolarization of neural cells, implicated in several neuropathological conditions. The breakdown of brain homeostasis promotes significant hemodynamic and metabolic alterations, which impacts on neuronal function. In this work we aimed to develop an innovative multimodal approach, encompassing metabolic, electric and hemodynamic measurements, tailored but not limited to study SD. This was based on a novel dual-biosensor based on microelectrode arrays designed to simultaneously monitor lactate and glucose fluctuations and ongoing neuronal activity with high spatial and temporal resolution. In vitro evaluation of dual lactate-glucose microbiosensor revealed an extended linear range, high sensitivity and selectivity, fast response time and low oxygen-, temperature- and pH- dependencies. In anesthetized rats, we measured with the same array a significant drop in glucose concentration matched to a rise in lactate and concurrently with pronounced changes in the spectral profile of LFP-related currents during episodes of mechanically-evoked SD. This occurred along with the stereotypical hemodynamic response of the SD wave. Overall, this multimodal approach successfully demonstrates the capability to monitor metabolic alterations and ongoing electrical activity, thus contributing to a better understanding of the metabolic changes occurring in the brain following SD.